1990
DOI: 10.1111/j.1469-8137.1990.tb00928.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural and histochemical studies on interactions between Vitis vinifera L. and Uncinula necator (Schw.) Burr.

Abstract: SUMMARYHost-parasite interactions between the grapevine Vitis vinifera L. and the powdery mildew Uncinula necator (Schw.) Burr, were studied by light microscopy and histochemistry, scanning and transmission EM. The lobed appressoria (10/^m diam) of the fungus adhered to the host cuticle because of their shape and the production of a soluble adhesive substance. Each formed a penetration peg (0-3 //m diam) which, after penetration into the epidermal cell, developed into a globular haustorium consisting of a nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 47 publications
1
19
1
Order By: Relevance
“…It is also interesting to note that M. grisea is able to use hyphopodia to infect rice roots rather than the appressorium mediated method of penetration used on leaves (Sesma and Osbourn, 2004). Structures very similar to those identified in this study have also been reported for the foliar pathogens Erysiphe pisi and Ucinula necator (Falloon et al, 1989;Heintz and Blaich, 1990). In highlighting the inconsistency with naming these structures, the authors of both papers reported the presence of appressoria.…”
Section: Resultssupporting
confidence: 58%
“…It is also interesting to note that M. grisea is able to use hyphopodia to infect rice roots rather than the appressorium mediated method of penetration used on leaves (Sesma and Osbourn, 2004). Structures very similar to those identified in this study have also been reported for the foliar pathogens Erysiphe pisi and Ucinula necator (Falloon et al, 1989;Heintz and Blaich, 1990). In highlighting the inconsistency with naming these structures, the authors of both papers reported the presence of appressoria.…”
Section: Resultssupporting
confidence: 58%
“…These symptoms are due to the presence of hyphae producing conidiophores and conidia on the surface of the host tissue. The hyphae form lobed appressoria which produce a penetration peg that subsequently penetrates into the host epidermal cell and forms a haustorium via which the fungus absorbs nutrients from the host (Heintz and Blaich 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, an infection structure, termed a haustorium, is formed within the epidermal cell through which a dynamic exchange of signals and metabolites occurs between the pathogen and the host cell (Heintz and Blaich, 1990;Rumbolz et al, 2000). The process of penetration and haustorium formation in V. vinifera may be as short as 14 h under optimal conditions (Rumbolz et al, 2000).…”
mentioning
confidence: 99%